If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(c + 2) + 1 = 5c + -1 Reorder the terms: 3(2 + c) + 1 = 5c + -1 (2 * 3 + c * 3) + 1 = 5c + -1 (6 + 3c) + 1 = 5c + -1 Reorder the terms: 6 + 1 + 3c = 5c + -1 Combine like terms: 6 + 1 = 7 7 + 3c = 5c + -1 Reorder the terms: 7 + 3c = -1 + 5c Solving 7 + 3c = -1 + 5c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-5c' to each side of the equation. 7 + 3c + -5c = -1 + 5c + -5c Combine like terms: 3c + -5c = -2c 7 + -2c = -1 + 5c + -5c Combine like terms: 5c + -5c = 0 7 + -2c = -1 + 0 7 + -2c = -1 Add '-7' to each side of the equation. 7 + -7 + -2c = -1 + -7 Combine like terms: 7 + -7 = 0 0 + -2c = -1 + -7 -2c = -1 + -7 Combine like terms: -1 + -7 = -8 -2c = -8 Divide each side by '-2'. c = 4 Simplifying c = 4
| x^2+x=1.52 | | 509.8104=2*3.14*r^2+2*3.14*r*55.6 | | -7(-5k-7)=84 | | 5(k-3)=(k-5) | | (7x-15)1/3 | | 6(5/9) | | F(x)=(-6)+3 | | -1+20n+15=8n-10+6 | | 70-a=25 | | .05x+09(28000-x)=2400 | | -2+b=3 | | 52x=1/625x | | q=50-2p | | -1+20n+3=8n-10+6 | | 2y+3x+1=0 | | 9=-r | | 12x^2-6x=45 | | b+8b+1=19 | | 0=16t^2-40t-25 | | 100=(65000)x(1+0.016)100 | | r+r+8=14 | | -4(3(-5)-5)= | | F(x)=(x+5)-6 | | -4+35y-1=21y+18+5 | | (21y^5-5y^4-18y^3)/(3y^4) | | 3x-4x+5x-9x= | | f(x)=x^2-16x+67 | | r+r+8=6 | | =(65000)x(1+0.016)100 | | 6a-1=17 | | (y-3)(y-3)=2y^2+2y-12 | | s(t)=-16t^2+20t+6 |